Elucidating strategies used by clinical nurse leaders to facilitate fundamental care delivery: A qualitative study. (12th July 2022) - Mudd, Alexandra; Feo, Rebecca; McCloud, Christine; Conroy, Tiffany
Abstract: Aim: To investigate the strategies used by nurse leaders to facilitate fundamental care delivery in their clinical area. Design: An interpretative qualitative design study reported in line with the Consolidated Criteria for Reporting Qualitative Research (COREQ). Methods: Twenty‐four self‐identified nurse leaders from across Australia were interviewed between November 2020 and April 2021 to discuss their strategies for facilitating fundamental care. Data was analysed using inductive thematic analysis. Results: Nurse leaders' experience of facilitating fundamental care produced two major themes, delivery of fundamental care (comprising three sub‐themes: valuing fundamental care, understanding and developing staff capacity and supportive relationships), and monitoring of fundamental care (including three sub‐themes: visibility in the clinical area, embedding fundamental care in the practice setting and specific direct actions). Conclusion: Facilitating fundamental care delivery is complex. This study highlighted the importance of nurse leaders' individual characteristics, and nurse leaders' ability to establish and maintain relationships alongside the role of informal and formal monitoring of fundamental care delivery. Impact: Findings from this study build on existing research into fundamental care and contribute to our understanding of the role, characteristics and actions of nurse leaders to facilitate fundamental care. The results demonstrate the complexity and intricacy of nursing leadership to facilitate fundamental care, and that a dynamic 'thinking and linking' approach is required. The results show individualized practice which may create challenges for new nurse leaders seeking guidance, and for monitoring nurse leader activity. Further research is advocated to explore insights and tools to optimize nurse leaders' endeavours in facilitating fundamental care. Patient or Public Contribution: This study was designed using insights generated from patient and public involvement in nursing leadership and fundamental care.